Pelatihan dan Pendampingan Implementasi PBJT atas Jasa Makanan dan Minuman dalam Meningkatkan Kepatuhan Perpajakan pada RM. Griyo Keprabon - Erma Wulan Sari; Aliffianti Safiria Ayu Ditta; Yolanda Dhamayanti (Universitas PGRI Madiun, 2026)
The Regional Tax on Certain Goods and Services (PBJT) for food and beverage services is one of the important sources of Regional Original Revenue (PAD) that plays a significant role in supporting regional development. Since the enactment of Law Number 1 of 2022 concerning Fiscal Relations between the Central Government and Regional Governments (HKPD), many restaurant business operators have continued to face challenges in understanding the mechanisms for tax calculation, collection, recording, and reporting. This community service activity aimed to enhance tax knowledge and compliance at RM. Griyo Keprabon through tax management training and assistance. The methods employed included observation, counseling, training, discussion, and hands-on assistance in implementing PBJT management for food and beverage services. The results demonstrated an improvement in the partner's understanding of restaurant tax regulations, tax calculation procedures, transaction recording, and tax reporting in accordance with applicable regulations. The program also contributed to the establishment of more organized tax administration practices, thereby supporting increased business tax compliance. Therefore, the training and assistance provided were effective in helping the partner achieve more efficient, transparent, and accountable tax management.